Fenomena Verbal Abusive Dan Dampaknya Terhadap Spritual Intellegence (Studi Fenomenologi di Dsn.Jatimenok Ds. Rejosopinggir Tembelang Jombang) - Arini, Aida (Universitas Yudharta Pasuruan, 2023)
verbal abuse is abusive behavior in verbal form, one of which is misuh. Verbal abuse, msuh have become a phenomenon in Jatimenok, Rejosopinggir Tembelang Jombang among the general public and children. This phenomenon can be in many places. It is done by children to express their feelings to their colleagues or parents. One of the factors is the bad environment. An environment teaches them to do misuh, sometimes from parents who are used to misuh and parents around them. the child utters abusive verbal, hate it. So environmental conditions are unfavorable due to low levels of education, minimal religious knowledge, and awareness of social morals and the impact of verbal abuse on children's emotional development which has greater consequences in the form of damage to social order which must be repaired from an early age, through Islamic parenting to provide knowledge and insight. to parents about the urgency of morals and the negative impact to spiritual intelegence as moral decadency and disrespect to parents and society as well as assistance to parents to be positive role models for children and be wise in reprimanding them when they commit verbal abuse, abuse without intimidation.